2009
DOI: 10.1124/mol.109.054791
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of Imidazoacridinones Facilitating Antitumor Activity Are Crucial for Substrate Recognition by ABCG2

Abstract: Symadex is the lead acridine compound of a novel class of imidazoacridinones (IAs) currently undergoing phase II clinical trials for the treatment of various cancers. Recently, we have shown that Symadex is extruded by ABCG2-overexpressing lung cancer A549/K1.5 cells, thereby resulting in a marked resistance to certain IAs. To identify the IA residues essential for substrate recognition by ABCG2, we here explored the ability of ABCG2 to extrude and confer resistance to a series of 23 IAs differing at defined r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Certain acridinone derivatives are new potent cytotoxic agents which have shown promise against leukemia, melanoma, breast cancer and others [28, 29]. IAs apparently function via several mechanisms such as arresting the cell in the G 2 phase of the cell cycle, inducing cell death, inhibiting cleavable complexes of topoisomerase II with DNA, intercalating into DNA and binding to the minor groove [2931].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain acridinone derivatives are new potent cytotoxic agents which have shown promise against leukemia, melanoma, breast cancer and others [28, 29]. IAs apparently function via several mechanisms such as arresting the cell in the G 2 phase of the cell cycle, inducing cell death, inhibiting cleavable complexes of topoisomerase II with DNA, intercalating into DNA and binding to the minor groove [2931].…”
Section: Introductionmentioning
confidence: 99%
“…One of the dominant mechanisms of MDR is mediated by efflux pumps of the ATP-Binding Cassette (ABC) superfamily which exert enhanced extrusion of various hydrophobic and amphiphilic cytotoxic drugs [28, 3234]. One of the strategies to overcome MDR is by using novel NP systems [33].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, identifying the structural elements within peptide epoxyketone-based chemical structures that render them Pgp substrates may be an important strategy for evading Pgp-mediated drug efflux and overcoming drug resistance. In fact, we have shown that small chemical modifications can generate analogs of a class of topoisomerase drug inhibitors, i.e., imidazoacridinones, which were no longer substrates for the drug efflux transporter BCRP (Bram et al, 2009). Indeed, Zhou et al (2009) showed that modifications in the N-cap of the peptide epoxyketone backbone, in particular introducing (5-Me)-3-isoxazole or 2-(S)-tetrahydrofuran, retained chymotrypsinlike proteasome activity while Pgp substrate activity was abolished.…”
Section: Resistance To Epoxyketone-based Proteasome Inhibitors 179mentioning
confidence: 99%
“…Recently we have shown that a class of cytotoxic drugs known as IAs including C-1371, C-1492, C-1309 and C-1336 are bona fide transport substrates of ABCG2 [12]. We therefore hypothesized that IAs may be actively sequestered and concentrated within ABCG2-rich EVs.…”
Section: Resultsmentioning
confidence: 99%
“…IAs bearing a hydroxyl group at one of the R1, R2, R3 positions in the proximal IA ring, including C-1371, C-1492 and C-1309 were recognized as ABCG2 transport substrates and were actively extruded from ABCG2-overexpressing MDR cells [12]. In contrast, IAs lacking a hydroxyl group such as C-1266 and C-1375 were not recognized by the MDR efflux pump ABCG2.…”
Section: Introductionmentioning
confidence: 96%